2004
DOI: 10.1385/mb:26:3:249
|View full text |Cite
|
Sign up to set email alerts
|

The Comet Assay for DNA Damage and Repair: Principles, Applications, and Limitations

Abstract: The comet assay (single-cell gel electrophoresis) is a simple method for measuring deoxyribonucleic acid (DNA) strand breaks in eukaryotic cells. Cells embedded in agarose on a microscope slide are lysed with detergent and high salt to form nucleoids containing supercoiled loops of DNA linked to the nuclear matrix. Electrophoresis at high pH results in structures resembling comets, observed by fluorescence microscopy; the intensity of the comet tail relative to the head reflects the number of DNA breaks. The l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
1,355
2
68

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 2,444 publications
(1,443 citation statements)
references
References 39 publications
18
1,355
2
68
Order By: Relevance
“…During this 24-hour period, cells were continuously removing and repairing BPDE-induced DNA damages. Therefore, the level of DNA breaks in our study after 24-hour incubation should reflect the overall host NER capacity [21,25]. In support of this notion, we previously performed experiments using various XP cells deficient in XPC, XPA, or XPD genes.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…During this 24-hour period, cells were continuously removing and repairing BPDE-induced DNA damages. Therefore, the level of DNA breaks in our study after 24-hour incubation should reflect the overall host NER capacity [21,25]. In support of this notion, we previously performed experiments using various XP cells deficient in XPC, XPA, or XPD genes.…”
Section: Discussionsupporting
confidence: 58%
“…It has been widely use to quantify DNA damages in peripheral blood lymphocytes (PBLs) challenged by mutagens such as BPDE, NNK, H 2 O 2 , and gamma-radiation [20]. Comet assay is also used to evaluate the in vitro host DRC [21]. In this study, to test the hypothesis that three common polymorphisms in XPC gene, Ala499Val (C→T), PAT (-/+), and Lys939Gln (A→C), modulate DRC, we determined the DNA damage/repair capacity in PBLs challenged by BPDE and gamma-radiation using alkaline comet assay in 476 healthy subjects.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that freezing of lymphocytes does not increase DNA strand breaks as compared to those of freshly isolated lymphocytes, and that fresh and frozen lymphocytes responded almost identically to hydrogen peroxide (Duthie et al, 2002). Visual scoring system used in this study reported to be accurately corresponding to the data that are measured by computer image analysis in human lymphocytes (Collins, 2004), in equine lymphocyte (Marlin et al, 2004) and in canine and feline leukocytes (Heaton et al, 2002). The method used for visual scoring involves classifying comets into four categories on the basis of the perceived length of migration and relative proportion of DNA in the tail.…”
Section: Discussionmentioning
confidence: 56%
“…The genome-protective eff ect of xanthohumol against oxidative DNA damage induced by H 2 O 2 was evaluated using the yeast comet assay. The yeast comet assay is a well-established, simple, versatile, sensitive and inexpensive technique used to assess DNA oxidative damage quantitatively and qualitatively in eukaryotic cell populations (30)(31)(32)(33). Yeast spheroplasts were incubated with diff erent xanthohumol concentrations and 10 mM H 2 O 2 in S buff er (containing 1 M sorbitol) in order to maintain osmotic protection.…”
Section: Xanthohumol Protects Yeast Cells From Dna Damage Induced By mentioning
confidence: 99%